2015
DOI: 10.7314/apjcp.2015.16.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Role of +405C>G and +936C>T Polymorphisms of the Vascular Endothelial Growth Factor Gene and Risk of Esophageal Cancer in the Kashmiri Population

Abstract: micrograms/kg) and N nitrosopipecolic acid (NPIC) (5870 micrograms/kg) which may impart risk for EC in this area (Siddiqi et al., 1988

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…VEGF gene polymorphisms may influence the gene expression and affect plasma VEGF levels (Renner et al, 2000;Watson et al, 2000). Previous studies reported that VEGF gene polymorphisms may influence the development of many solid tumors, such as esophageal cancer, colorectal cancer, renal cell carcinoma, and breast cancer (Yao et al, 2014;Jannuzzi et al, 2015;Ma et al, 2015;Qasim et al, 2015). Qasim et al (2015) conducted a case-control study to investigate the role of the VEGF +936C/T and +404C/G polymorphisms on the risk of esophageal cancer, and they found a significant association between the VEGF +936C/T and +404C/G polymorphisms and esophageal cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF gene polymorphisms may influence the gene expression and affect plasma VEGF levels (Renner et al, 2000;Watson et al, 2000). Previous studies reported that VEGF gene polymorphisms may influence the development of many solid tumors, such as esophageal cancer, colorectal cancer, renal cell carcinoma, and breast cancer (Yao et al, 2014;Jannuzzi et al, 2015;Ma et al, 2015;Qasim et al, 2015). Qasim et al (2015) conducted a case-control study to investigate the role of the VEGF +936C/T and +404C/G polymorphisms on the risk of esophageal cancer, and they found a significant association between the VEGF +936C/T and +404C/G polymorphisms and esophageal cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular endothelial growth factor (VEGF), is one of the key growth factors, that regulates vascular development and angiogenesis and plays an important role in the growth and progression of human cancers, including lung carcinom a [9,10]. The current evidence indicated that VEGF gene polymorphism is associated with the susceptibility of some cancer s [11]. There is lack of good diagnostic methods that predict the risk of lung cancer, and which etiology is complicated and not clear.…”
Section: Introductionmentioning
confidence: 99%